In Vitro Evaluation of Five Core Materials - Steven Gu, PhD;1 Brian J. Rasimick, BS;2 Allan S. Deutsch, DMD;3 (Journal of Prosthodontics, 2007)
This in vitro study determined the fracture strength of five core materials supported by two different endodontic dowels.